The effect of power point presentation to the development of higher-order thinking skills in science - Princesa, Maria Analou L. (San Miguel, Iriga City: University of Saint Anthony, 2016)
The effect of power point presentation to the development of higher-order thinking skills in science.
Includes bibliographical references.
English
Keywords: Science